Structured education programme on Patient Controlled Analgesia (PCA) for orthopaedic patients - Ho, Siew Eng; Ho, Christopher Chee Kong; Zainah Mohamed,; Indra,; Jaafar Md Zain,; Choy, Yin Choy; Ismail Mohd Saiboon, (Fakulti Perubatan, UKM, 2016)
Patient-controlled analgesia (PCA) via an infusion pump enables patient to administer their own analgesia. The aim of this study was to evaluate the effect of an educational programme in managing post-operative pain and satisfaction on PCA following orthopedic surgery. A pre-test and post-test interventional study design with implementation of patient education programme on PCA was provided to 54 respondents. The control group received conventional PCA briefing from the Acute Pain Service protocol. Pain intensity was measured at 2 hrs, 6 hrs and 24 hrs following surgery and pre-test and post-test of the Revised American Pain Society Patient Outcome Questionnaire (APS-POQ-R) was administered. There was difference in respondents’ level of pain score among the study respondents’ medians for control group at 2 hrs, 6 hrs and 24 hrs following surgery and they were 7.00 (IQR=3.00), 5.00 (IQR=2.00) and 3.00 (IQR=2.00); intervention group at 2 hrs, 6 hrs and 24 hrs following surgery were 6.00 (IQR=2.00), 3.00 (IQR=1.00) and 1.00 (IQR=1.00) respectively. There were significant differences in median of pain score between intervention and control group at 2 (U=142.0, p<0.05), 6 (U=150.50, p<0.05) and 24 (U=120.00, p<0.05) hrs following surgery. There were statistically significant differences (p<0.05) in the median of patient’s pain severity at all pain levels i.e. least pain, worst pain, and severe pain between intervention and control group (least pain, U=219.50, p<0.05; worst pain, U=117.0, p<0.05; severe pain, U=49.0, p<0.05). In conclusion, patients who received pre-operative structured education programme showed improvement in managing post-operative pain and satisfaction on PCA after orthopedic surgery.